Principles and techniques in combinatorics solutions manual - Foo, Kean Pew (World Scientific, 2019)
"The solutions manual provides comprehensive yet elementary solutions to each of the 489 problems that appeared in the textbook. The solutions manual contains full solutions to each problem in the parent textbook. The solutions to each problem are written from a first principles approach, which would have further augment the understanding of the important and recurring concepts in each chapter. Moreover, the solutions are written in a relatively self-contained manner, with very little undergraduate mathematics assumed. In that regard, the solutions manual appeals to a wide range of readers, from secondary and junior college students, undergraduates, to teachers and professors"